Virtual Reality and 3D Simulation in the Treatment of Pediatric Patients with Central Nervous System Tumors - Mastronuzzi, Angela; Baldo, Giada Del; Carai, Andrea (International Journal of Pediatrics and Child Health, 2023)
Pediatric central nervous system tumors are the primary solid malignancies in children and remain a leading cause of mortality in infancy. Advances in pediatric neuro-oncology, driven by molecular oncology research, emphasize the critical need for high-quality pathological tissue to support advanced molecular investigations. However, the vast heterogeneity of these tumors requires precise discrimination of collection sites, aligning with preoperative imaging data. Surgical resection, a pivotal step in diagnosis and treatment, could result in potential morbidities influencing children’s neurological status. This, in turn, affects the feasibility of subsequent oncological treatments, influencing overall prognosis and quality of life. To address these challenges, technological tools enhance neurosurgeon orientation in pre-surgical planning and resection. While stereotactic navigation systems reduce morbidity, limitations persist in providing only two-dimensional anatomical information. Recent developments in 3D surgical simulation and virtual reality revolutionize procedural planning, offering real-time integration with intraoperative navigation systems. Beyond surgery, virtual reality has potential in case discussions, preoperative planning, and operative guidance, aiming to improve care and patient outcomes. The virtual reality experience, coupled with detailed anatomical visualization, facilitates meticulous surgical strategy planning for minimal invasiveness. Despite expanding literature on virtual reality applications in neurosurgery, pediatric neurosurgical oncology experiences remain limited. Scientific evaluation of simulation systems’ impact on techniques and outcomes, combined with advances in neuroimaging, offers promise for adapting surgical approaches based on neoplastic brain lesion behavior. In conclusion, incorporating 3D surgical simulation and virtual reality technologies in pediatric neurosurgical oncology holds substantial benefits, offering improved procedural planning, enhanced precision, and patient-specific adaptation. Despite limited reported experiences, the compelling advantages underscore the need for further exploration and consideration in the evolving landscape of pediatric neuro-oncology.